Peningkatan Minat Belajar dan Hasil Belajar Siswa Melalui Model Inkuiri Terbimbing Dipadu Kooperatif Jigsaw Kelas X IS-3 SMA Batik 1 Surakarta Tahun Pelajaran 2013/2014 - Risaul Adika; Maridi Maridi; Bowo Sugiharto (Universitas Sebelas Maret, 2014)
This study aims to improve the student’s learning outcomes and learning interest in biology class X IS-3 SMA Batik 1 Surakarta with guided inquiry combined with cooperative jigsaw model. This research is Classroom Action Research with 3 cycles of action. Each cycle consists of four phases: planning, action, observation, and reflection. The subjects were students of class X IS-3 SMA Batik 1 Surakarta academic year 2013/2014. The data was obtained through test technique with multiple choice and non-test technique with observation, interview, and documentation. Data result of observations, interviews, and documentation was analyzed by descriptive qualitative analysis techniques while data validation using triangulation technique. The result of the research showed that the implementation of the class action through the use of guided inquiry combined with cooperative jigsaw model can improve learning interest and learning outcomes of students in learning biology. It is based on the results of written tests, observation, and interviews. The average percentage students’ attainment in each indicator of student interest learning in pre-cycle was 45.83%, then increased to 74,16% in first cycle (worked up 28.33%), then increased to 88.11% in second cycle (worked up 13.95%). The average percentage students’ attainment in students' knowledge aspects in pre-cycle was 50%, then increased to 62.50% in first cycle (worked up 12.50%), then increased to 92.50 % in second cycle (worked up 30%). The average percentage students’ attainment in each indicator of students’ skills in pre-cycle was 36.87%, then increased to 61.25% in first cycle (worked up 24.38%), then increased to 80.83 % in second cycle (worked up 19.58%). The average percentage students’ attainment in each indicator of students’ learning attitude in pre-cycle was 48.25%, then increased to 62.25% in first cycle (worked up 14.25%), then increased to 77.25% in second cycle (worked up 15%). The results of student and teacher interviews indicated that the use of guided inquiry combined with cooperative jigsaw model provide flexibility for students to find their own concept with fun learning. Based on the result above, it can be concluded that the use of guided inquiry combined with cooperative jigsaw model can improve students’ learning interest and learning outcomes in class X IS-3 SMA Batik 1 Surakarta academic year 2013/2014 to study biology. Key Words: guided inquiry, cooperative jigsaw, learning interest, learning outcomes